INOVASI DIGITAL MARKETING DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA MARKETPLACE SHOPEE - Purwati , Devid (Universitas Terbuka, 2024)
This research was conducted in order to find out what digital marketing innovations can influence consumer buying interest in the shoope marketplace. Technological developments in today's world are growing very rapidly, making it easier for people to access and carry out the buying and selling process using digital media as a means of buying and selling. So that online buying and selling comes as a new innovation in the world of marketing and is the main choice for producers to promote products or services that will be marketed through online media on the marketplace. The buying and selling process in the marketplace, which is currently widely accessed and in demand by the public, one of which is the shoope application which is currently the most frequently visited by the public. Marketing through digital marketing on the shoope marketplace greatly facilitates the buying and selling process without having to meet directly with consumers. Business actors also make efforts to implement good strategies to influence consumer buying interest. Consumer buying interest in this study is influenced by the quality and uniqueness of the products being promoted, good service and product reviews will greatly affect the sale of marketed products In this study, researchers used qualitative methods that were delivered descriptively using relevant books, web, journals. Based on the research results obtained, there are many factors that can affect consumer buying interest in the shoope marketplace including using maximum application features, providing good service and interesting product reviews, always maintaining product quality and good marketing techniques have a positive influence and can affect consumer buying interest.